2022
DOI: 10.3389/fpls.2022.1032820
|View full text |Cite
|
Sign up to set email alerts
|

Climate change impedes plant immunity mechanisms

Abstract: Rapid climate change caused by human activity is threatening global crop production and food security worldwide. In particular, the emergence of new infectious plant pathogens and the geographical expansion of plant disease incidence result in serious yield losses of major crops annually. Since climate change has accelerated recently and is expected to worsen in the future, we have reached an inflection point where comprehensive preparations to cope with the upcoming crisis can no longer be delayed. Developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 173 publications
1
6
0
Order By: Relevance
“…Earlier, we demonstrated that indoleamines were crucial in mitigating climate stress and improving reproduction processes in cold‐sensitive hazelnut cultivars and the modulation patterns in endogenous indoleamine titers could be correlated to poor performances of cold‐sensitive hazelnut cultivars grown in the colder continental climate 19,71,72,76–79 . Our study in the hazelnut also suggested a powerful mitigation when the dormant stem cuttings were exposed to sudden summer‐like conditions in the presence of TRP or SER in parallel to improved flowering 19 .…”
Section: Discussionsupporting
confidence: 59%
“…Earlier, we demonstrated that indoleamines were crucial in mitigating climate stress and improving reproduction processes in cold‐sensitive hazelnut cultivars and the modulation patterns in endogenous indoleamine titers could be correlated to poor performances of cold‐sensitive hazelnut cultivars grown in the colder continental climate 19,71,72,76–79 . Our study in the hazelnut also suggested a powerful mitigation when the dormant stem cuttings were exposed to sudden summer‐like conditions in the presence of TRP or SER in parallel to improved flowering 19 .…”
Section: Discussionsupporting
confidence: 59%
“…Conversely, the lesion size on the resistant cultivar was tripled when incubated at 28ºC compared to those at 21ºC. The reduction of the lesion size on the susceptible cultivar may result from lower pathogen virulence, enhanced physiological vigor of the plant (eg., leaf area), and stomatal closure, which reduces pathogen penetration 26,27 . Furthermore, the impact of temperature on the resistance gene and its diminished e cacy might be cited as a potential cause for the larger spot size realized at 28ºC compared to 21ºC.…”
Section: Investigating the Metabolite Pro Le Via Multivariate Analysismentioning
confidence: 99%
“…Under ever-changing environmental conditions, plants have to deal with several abiotic and biotic adversities, which frequently have a negative impact on their productivity and growth [1]. For that reason, plants have evolved complex functional and genetic adaptation mechanisms that can be activated to counteract/cope with oxidative reactions, while continuing growth (even though at a decreased rate) and reaching a fruitful yield [2]. According to Munns and Millar [3], these mechanisms are related to taking up vital resources, while storing and supplying them to various plant parts, to produce the energy required for cellular functions, maintain tissue integrity, transmit signals among plant parts, arrange structural assets under changed environmental conditions, and shape-shift through development.…”
Section: Introductionmentioning
confidence: 99%